Architecture-Driven Integration of Energy Harvesting in Resource-Constrained IoT Systems Using the Unified Architecture Framework (UAF) - Green, Christopher (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
As the use of resource constrained IoT becomes more prevalent, it relies more often on energy harvesting capabilities for sustaining autonomous operations in uncertain power environments. However, incorporating energy harvesting functionality poses challenges as a result of introducing strong interdependencies between energy generation, storage, operational behavior, security measures, and mission availability. Current methods for addressing the problem usually deal with these aspects on a component or subsystem level and therefore lack cross-domain interaction visibility and understanding, which results in an increased probability of integration errors. In this paper, we propose the architecture driven approach for energy harvesting integration by means of the Unified Architecture Framework (UAF). Instead of being considered separately, energy availability will be addressed as an architectural constraint at a system level in a meta-model driven environment. Through the instantiation of capabilities, operations, resources, security, and standards constructs within a semantic baseline, we show the ability to trace energy- security-mission dependencies across multiple domains. This paper describes how harvested energy variance affects system operations, communications, cybersecurity, capabilities, and system availability. The findings suggest that incorporating energy and cyber security principles in an integrated architectural framework can overcome the problem of fragmentation, enhance overall system reasoning, and facilitate energy-conscious joint design of functional and security-related features. The study provides a scalable architectural basis for the design and evaluation of secure IoT systems with energy constraints.